2020
DOI: 10.3892/etm.2020.8630
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide ameliorates COCl2-induced oxidative stress and apoptosis in H9C2 cells via regulating cell autophagy

Abstract: Protective effects of liraglutide on H9C2 cells cultured using CoCl 2 and its mechanism of action were investigated. Hypoxia model was established using CoCl 2-treated H9C2 cells. With liraglutide as the treatment factor, apoptosis, changes in nitric oxide (NO) and reactive oxygen species (ROS) activity, mitochondrial membrane potential and change in cell autophagy level were detected via Hoechst staining, enzyme-linked immunosorbent assay (ELISA), polymerase chain reaction (PCR) and western blotting (WB), res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…our results suggested that LRG at 100 and 1000 nmol/L for 72h promoted cell viability, whereas higher concentration of LRG (10000 nmol/L) showed signi cant toxicity to MC3T3-E1 cells. Cytotoxicity of LRG was determined by the release of lactate dehydrogenase and showed that no signi cant cytotoxicity in the 1-1000 nmol/L concentration range (Pang et al 2020). Combined with the results of mRNA expression analysis of GLP1R, pretreatment with 100nmol/L LRG for 48h was selected as the optimal condition for subsequent cell experiments, which was consistent with the research results of Sun and Wu et al (Sun et al 2020;Wu et al 2017).…”
Section: Discussionsupporting
confidence: 79%
“…our results suggested that LRG at 100 and 1000 nmol/L for 72h promoted cell viability, whereas higher concentration of LRG (10000 nmol/L) showed signi cant toxicity to MC3T3-E1 cells. Cytotoxicity of LRG was determined by the release of lactate dehydrogenase and showed that no signi cant cytotoxicity in the 1-1000 nmol/L concentration range (Pang et al 2020). Combined with the results of mRNA expression analysis of GLP1R, pretreatment with 100nmol/L LRG for 48h was selected as the optimal condition for subsequent cell experiments, which was consistent with the research results of Sun and Wu et al (Sun et al 2020;Wu et al 2017).…”
Section: Discussionsupporting
confidence: 79%
“…CoCl 2 is a well-known hypoxia-mimetic chemical reagent in vitro and in vivo [26,27]. Consistently, treatment with CoCl 2 at different concentrations decreased H9c2 viability and increased H9c2 apoptosis [28]. Importantly, the study revealed the significant protective effects of nesfatin-1 on CoCl 2 -induced cell injury.…”
Section: Discussionsupporting
confidence: 56%
“…ROS are an important indicators of oxidative damage and the early stage of apoptosis ( Wang et al, 2019 ; Pang et al, 2020 ). CLSM images showed that, compared with the control group, there was a significant increase in intracellular ROS under the induction of 1.4 mmol/L CoCl 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have reported that ROS contributes to intracellular Ca 2+ overload ( Yu et al, 2014 ; Pang et al, 2020 ). Consistent with these results, ROS overproduction induced by CoCl 2 in the current study elevated the level of cytosolic Ca 2+ .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation